Desenvolvimento de espumas para isolamento térmico a partir de resíduos de vidro e hidróxido de sódio - Silva, Robson Couto da (2019)
World population growth and a faster consumption of goods bring energy shortage and a lot of environmental liabilities. Thereby, research, development and innovation sectors must consider the ecological aspects in their studies. Reuse of wastes for new applications is an alternative route to solve this issue and glass wastes stand out in this aspect. Due to their chemical compositions, glass waste can be used as raw materials in several industrial sectors, for example in the manufacture of glass foams. Due their high porosity, glass foams can be used in different ways, such as filtration, biomaterials and thermal insulation. However, during the glass foams manufacturing, conventional foaming agents release pollutants gases into the atmosphere. Thus, the aim of this work was to obtain glass foams for thermal insulation application by a route that eliminates such a problem. Firstly, a study was carried out to understand the reaction mechanism and the process variables in order to know the essential information for the development and later to evaluate the properties of the synthesized material. In this research, soda-lime glass waste was used as composition bottom, along with sodium hydroxide (foaming agent) and borax pentahydrate (flow agent). Glass foams were characterized by Archimedes method, differential thermal analysis, thermogravimetry analysis combined with mass spectroscopy, optical dilatometry, X - ray diffraction, infrared spectroscopy and scanning electron microscopy. Two factorial designs were performed in order to evaluate the influences of composition and of processing parameters on material properties. Thermal conductivity measurements were performed from the temperature gradient between two plates, following the Fourier Law. Results showed that at the glass transition temperature (587 oC), the crystallization of a hydrated sodium and calcium silicate phase was observed. When the composition was heated to a temperature above the softening point (686 oC), the foaming occurred due to steam released from the hydrated sodium and calcium silicate and a new phase called devitrite was formed. Such a phase remained stable until the end of the sintering cycle. Glass foams with geometric density of 0.135 g/cm3 and total porosity of 92.37% were obtained at 750 °C. Foaming temperature and amounts of sodium hydroxide and borax were the main process control parameters. Thermal conductivity varied from 0.046 to 0.061 W/m.oC. Thus, results showed that steam is the only gas involved in the foaming process, which indicates the proposed approach is environmentally friendly. Finally, glass foams from glass waste and sodium hydroxide present potential for application as thermal insulation.